Polarization of the Fulling-Rindler Vacuum in Models with Compact Dimensions - Kotanjyan, V. Kh.
We investigate the expectation value of the field squared for a charged scalar field in the Rindler spacetime with toroidally compact dimensions. The expectation values are compared for the Fulling-Rindler and Minkowski vacua. For general phases in the periodicity conditions on the field operator along compact dimensions, integral representations are provided for the difference of those expectation values. The vacuum expectation value of the field squared is an even periodic function of the magnetic flux enclosed by compact dimensions. Simple asymptotic expressions are given near the Rindler horizon and for small accelerations. We show that the mean field squared in the Fulling-Rindler vacuum is smaller than the respective expectation value for the Minkowski vacuum.
Keywords: Physics